2014
DOI: 10.1364/oe.22.025084
|View full text |Cite
|
Sign up to set email alerts
|

Optical computation of the Laplace operator using phase-shifted Bragg grating

Abstract: Diffraction of a 3D optical beam on a multilayer phase-shifted Bragg grating (PSBG) is considered. It is shown that the PSBG enables optical computation of the spatial Laplace operator of the electromagnetic field components of the incident beam. The computation of the Laplacian is performed in reflection at normal incidence. As a special case, the parameters of the PSBG transforming the incident Gaussian beam into a Laguerre-Gaussian mode of order (1,0) are obtained. Presented numerical results demonstrate hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
65
0
7

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(72 citation statements)
references
References 17 publications
0
65
0
7
Order By: Relevance
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was shown that such gratings have a high efficiency and can significantly reduce the size of the projection devices used in mobile phones, etc. Modern computational and technological capabilities allow colleagues and students of I. N. Sissakian to transfer from the tasks of diffractive optics to the problems of diffractive nanophotonics [122][123][124][125][126][127][128][129][130][131].…”
Section: Resultsmentioning
confidence: 99%
“…These results open up the prospects of solving one of the main tasks of computer optics -implementation of optical calculations [124][125][126][127] and lay the intellectual foundations of advanced information technologies [131]. Finally, we mention two practical applications of computer optics elements: protective holograms [132][133] and optical filters for professional and amateur photography [134] …”
Section: Resultsmentioning
confidence: 99%
“…Fast and stable optical computation based on the micro-waveguides with loss using the operator marching method (OMM) has been reported to solve the Helmholtz equation efficiently with complex refractive index or wavenumber [5]. This is followed by the development of optical computation of the spatial Laplace operator on the electromagnetic field components of the incident beam using the phased-shifted Bragg grating (PSBG) [6]. In order to accurately compute optical wave propagation in the inhomogeneous waveguides, a modified operator marching method based on a new treatment for local base transformation was proposed [7].…”
Section: Introductionmentioning
confidence: 99%
“…Traditionally, optical analog computing in the spatial domain uses a bulky system of lenses and filters18. Recently, there are significant efforts seeking to miniaturize such computing elements down to a single wavelength or even subwavelength scale1920212223242526272829. In particular, Silva et al 19.…”
mentioning
confidence: 99%